Analysis of Employee Engagement Using Aon Hewitt's Model: Study of Mow Company - Maulana, Diki; Pangestu, Aria Bayu (Journal of Innovation, Business and Entrepreneurship, 2019)
Food is one of basic human needs, so the demand of food will never stop which means there is a huge opportunity. Mow founder also very passionate about food that made Mow created to start a food entrepreneurship. After this business start running, one particular problem has arisen which is the motivation of the people engage in Mow itself. Mow participating in many trading activities, Mow encountered many problems, such as: Losses, Lack of capital, and the relationship between colleagues. From that problem, employee engagement is something that must be research to increase employee motivation problem. So this research is aim to find low score of employee engagement that can be improved in Mow company. This research used Explanatory Sequential Mixed method that involved Questionnaire as Quantitative and Focus Group Discussion (FGD) as Qualitative. he result has shown that the lowest score of employee engagement based on Aon Hewitt’s Model that found in the Mow company are Managing Performance Driver with 2.0 that indicates disengagement and also co-workers driver with 2.0 in second statement, contains close relationship between colleagues.Keywords: Employee Engagement, Motivation, Mow, Score, Variable.